The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1128/iai.71.4.1903-1910.2003
|View full text |Cite
|
Sign up to set email alerts
|

M Type 1 and 3 Group A Streptococci Stimulate Tissue Factor-Mediated Procoagulant Activity in Human Monocytes and Endothelial Cells

Abstract: Streptococcal toxic shock syndrome (StrepTSS) is an invasive infection characterized by marked coagulopathy, multiple organ failure, and rapid tissue destruction and is strongly associated with M type 1 and 3 group A streptococci (GAS). Initiation of the coagulation cascade with formation of microvascular thrombi contributes to multiple organ failure in human cases of gram-negative bacteremia; however, little is known regarding the mechanism of coagulopathy in StrepTSS. Thus, we investigated the abilities of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Interestingly, differences between these serotypes and their capacity to interact with endothelial cells have been observed. Bryant and co-workers (33) found that M3 GAS are able to specifically interact with endothelial cells, resulting in a tissue factor-mediated procoagulant response by these cells. Furthermore, it was shown that M3 GAS were more efficiently internalized by HUVEC compared with an M2 serotype strain (7).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, differences between these serotypes and their capacity to interact with endothelial cells have been observed. Bryant and co-workers (33) found that M3 GAS are able to specifically interact with endothelial cells, resulting in a tissue factor-mediated procoagulant response by these cells. Furthermore, it was shown that M3 GAS were more efficiently internalized by HUVEC compared with an M2 serotype strain (7).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GAS appeared to have an M-type-specific predilection for the TF-producing cells they stimulated. Specifically, M type 3 GAS elicited high levels of TF from endothelial cells but not monocytes, whereas with M type 1 strains, the converse was observed (21). This disparity existed although both M types elicited high levels of TNF-␣ and IL-8 from cultured monocytes (21) and enhanced leukocyte adherence molecule expression in endothelial cells (my unpublished observations).…”
Section: Mechanisms Of Coagulopathy In Invasive S Pyogenes and C Pementioning
confidence: 92%
“…Our recent investigations of this latter hypothesis demonstrated that killed, washed M type 1 and 3 strains of GAS isolated from patients with invasive infection stimulated the in vitro production of TF (21). Interestingly, GAS appeared to have an M-type-specific predilection for the TF-producing cells they stimulated.…”
Section: Mechanisms Of Coagulopathy In Invasive S Pyogenes and C Pementioning
confidence: 99%
“…Serotype-dependent activation of the extrinsic pathway of coagulation has been demonstrated in vitro, with heat-killed serotype M1 and M3, but not serotype M6, GAS strains triggering tissue factor synthesis on isolated human monocytes and cultured human umbilical vein endothelial cells, resulting in subsequent induction of procoagulant activity (373,379). Unlike the activation of the intrinsic pathway, which occurs at the cell surface, the activation of the extrinsic pathway is thought to occur via the interaction of the M protein with TLR2 following the release of M protein from the bacterial cell wall by bacterial or host-derived proteases (380)(381)(382).…”
Section: Dysregulation Of the Coagulation Systemmentioning
confidence: 99%
“…Transgenic mice lacking clotting factor V, deficient for thrombin generation, or lacking fibrinogen are more susceptible to invasive disease following subcutaneous challenge with GAS (372), highlighting the protective effect of proper coagulation in GAS infection. However, vascular thrombosis can promote hypoxia-induced tissue damage in necrotizing fasciitis (373). GAS activates the clotting cascade via both the intrinsic (contact activation) and extrinsic (tissue factor) pathways.…”
Section: Dysregulation Of the Coagulation Systemmentioning
confidence: 99%